Development of Modern Science and Classical Islamic Philosophy - Syarif Hidayatullah; Moh Ikbal; Ismail Ismail; M. Zuhri; Pioni Nurhaliza (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2024)
This article tells the story of the spirit of seeking and spreading knowledge in Islam which has been interestingly demonstrated by figures in the classical Islamic period. Carrying out translations, rewriting and copying of books from Persian to Arabic or Greek in the Islamic world. This article would like to inform you that current science and of course philosophy at large has the services of Muslim scientists and civilization in it, in terms of accelerating the transmission of classical thought into modern world thought. This research uses a qualitative method with a thematic analysis approach, this article succeeded in finding that Islam has a significant role in the 'formation' of modern science today.